Покчи эше: 1-2 классъёслы ватсаса лыдӟон книга / М. П. Лаврентьева, Е. Н. Дмитриева, В. Н. Ившин - Лаврентьева Мария Петровна (Удмуртия, 1992)
Экземпляры: ф-1 (ретроконверсия) / Инвентарный номер: 32416 / Цена: 24.00 / Сис.шифр: 83.3(2=А/=Я) / Авт.знак: Л 13 / ГРНТИ: 17 / ББК: 83.3(2=Удм)